2014
DOI: 10.1021/nl5002026
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Stemlike Cells with Fibrogenic Properties by Carbon Nanotubes and Its Role in Fibrogenesis

Abstract: We developed a three-dimensional fibroblastic nodule model for fibrogenicity testing of nanomaterials and investigated the role of fibroblast stemlike cells (FSCs) in the fibrogenic process. We showed that carbon nanotubes (CNTs) induced fibroblastic nodule formation in primary human lung fibroblast cultures resembling the fibroblastic foci in clinical fibrosis and promoted FSCs that are highly fibrogenic and a potential driving force of fibrogenesis. This study provides a predictive 3D model and mechanistic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Our results confirm previous studies which showed that exposure to longer SWCNTs induced increased toxic effects relative to shorter SWCNTs with exposure to longer nanotubes leading to an increase in the ROS generation (van Berlo et al, 2014), fibrosis (Luanpitpong et al, 2014b) and apoptosis (van Berlo et al, 2014), as well as reduction in cellular viability (Luanpitpong et al, 2014b; Manke et al, 2014). Further, our results confirm previous reports showing that the presence of metal impurities (i.e., Fe) in the nanotube samples resulted in higher cytotoxic and genotoxic effects (Aldieri et al, 2013), production of hydroxyl radicals, loss of intracellular low molecular weight thiols and accumulation of lipid hydroperoxides (Kagan et al, 2006), all by providing quantifiable differential measurements on the cell–cell and cell–substrate interactions without prior cellular manipulation or labeling (Kaiser et al, 2013; Song et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm previous studies which showed that exposure to longer SWCNTs induced increased toxic effects relative to shorter SWCNTs with exposure to longer nanotubes leading to an increase in the ROS generation (van Berlo et al, 2014), fibrosis (Luanpitpong et al, 2014b) and apoptosis (van Berlo et al, 2014), as well as reduction in cellular viability (Luanpitpong et al, 2014b; Manke et al, 2014). Further, our results confirm previous reports showing that the presence of metal impurities (i.e., Fe) in the nanotube samples resulted in higher cytotoxic and genotoxic effects (Aldieri et al, 2013), production of hydroxyl radicals, loss of intracellular low molecular weight thiols and accumulation of lipid hydroperoxides (Kagan et al, 2006), all by providing quantifiable differential measurements on the cell–cell and cell–substrate interactions without prior cellular manipulation or labeling (Kaiser et al, 2013; Song et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The greater capability of SWCNT to activate CAF-like cells over MWCNT in the present study is consistent with previous studies indicating that SWCNT induced greater interstitial pulmonary fibrosis and collagen deposition in vivo 4748 and induced higher fibroblast stem-like cells and 3D-fibroblastic nodules that resembled clinical fibroblastic foci in vitro 24. With respect to functionalization of CNTs, conflicting results have been reported.…”
Section: Discussionsupporting
confidence: 89%
“…The CNT doses used in the in vitro exposure studies were calculated based on in vivo exposure data normalized to the alveolar surface area in mice and humans2324. For example, the dose that induced positive in vivo biological response was 40 μg/mouse lung, which corresponds to 2 mg/kg body weight222526.…”
Section: Resultsmentioning
confidence: 99%
“…We calculated the above nanotube dose by employing an established methodology adopted by the National Institute of Occupational Safety and Health (NIOSH) that calculates human relevant dose for in vivo exposures. 7,37,38 Our in vivo dose of ~30 μ g/mouse corresponds to 60 mg/lung human burden (assuming 100 m 2 lung surface). This experimental dose can be reached in a worker after 2.25 months of exposure at 400 μ g/m 3 (inhalable concentration reported in a research facility) 39 or 7.5years of exposure at 10 μ g/m 3 (average inhalable MWCNT level in US facilities), 38 assuming lung deposition fraction of 30%, and a workday inhalation ventilation of 10 m 3 for a person working an 8 h shift.…”
Section: Resultsmentioning
confidence: 99%
“…16 For these reasons, the MWCNT global market is anticipated to reach 1 trillion dollars within the next decade. 7 However, increasing production and utilization of MWCNTs raise the risk of occupational and environmental human exposures. Given that MWCNTs still have a largely undefined safety profile, there is an urgent need to evaluate their health risks.…”
mentioning
confidence: 99%